Exploring the Development of Eco-Wellness Tourism Through Local Perspective: Qualitative Study in Gunung Dempo Tourism Area, Pagar Alam City, South Sumatra, Indonesia - Nanda Lovicha; Lastiani Warih Wulandari; Moch. Nur Syamsu (Lembaga Pengembangan Kinerja Dosen, 2025)
Development of eco- wellness Tourism in the Gunung Dempo tourist area, Pagar Alam City, South Sumatra is an effort to combine the concept of ecotourism with health tourism. The Gunung Dempo tourist area has extraordinary natural potential and strongly supports the implementation of the eco- wellness concept. tourism . This study aims to describe the role of eco- wellness tourism in the development of the Mount Dempo tourist area and analyzing the development of eco- wellness tourism in the Gunung Dempo tourist area in Pagar Alam City, South Sumatra. The research method used is a qualitative descriptive approach through observation, interviews, and documentation. The results of the study indicate that the main potential for developing eco- wellness tourism in the Gunung Dempo tourist area includes the beauty of various Gunung Dempo tourist attractions, and health-based tourism activities such as cycling, jogging , therapy at Tangga 2001, camping activities at the Dempo Botanical Gardens tourist attraction and the Dempo Skyline tour , breathing fresh air while seeing the view of the expanse of tea plantations and the towering Mount Dempo at the Bukit Tungguan Gunung Dempo tour, trekking at the peak of Mount Dempo, and other activities. There are obstacles such as lack of maintenance in facilities , human resources that have not been competent , lack of knowledge about eco-wellness tourism , and accessibility going to object tourism that needs to be improved to make it easier traveler visit area tour Mountain Dempo . The development strategy involves collaboration between the government, community, and private sector in improving tourism facilities, environmental sustainability, and digital-based promotion.